The Effect Of Training And Self-Esteem On Employee Performance With Job Satisfaction As An Intervening Variable In The Production Function Of Pt Kilang Pertamina Internasional Refinery Unit Iii Plaju - Almaurits Almaurits; Shelfi Malinda; Wita Farla Wk (UNIVED Press, 2026)
This study aims to analyze the effect of training and self-esteem on employee performance with job satisfaction as an intervening variable in the Production Function of PT Kilang Pertamina Internasional RU III Plaju. The study used a quantitative explanatory approach with primary data collection through questionnaires distributed to 207 respondents consisting of operators and supervisors. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results showed that training had a positive and significant effect on employee job satisfaction and performance. Self-esteem also had a positive and significant effect on job satisfaction and performance. In addition, job satisfaction had a positive effect on employee performance and partially mediated the relationship between training and performance, as well as between self-esteem and performance. These findings indicate that improved performance in high-risk work environments is not only determined by technical competence through training, but also by psychological factors that shape employee perceptions and job satisfaction. Therefore, strengthening the quality of training and self-esteem supported by effective job satisfaction is an important strategy to optimize employee performance in the oil and gas sector.